Application research on low cost support method for surrounding rock of broken section roadway in phosphate mine area - Xu, Mengchao; Li, Xiaoshuang; Wang, Jiawen; Cao, Mengzhen; Wang, Menglai; Li, Shujian (Frontiers in Earth Science, 2024)
Taking a phosphate mine in Yunnan as the engineering research background, the fractured rock mass of the No.1 belt roadway is selected as the research object. To reduce the cost of tunnel surrounding rock support and optimize construction technology, a combination of numerical simulation software Midas and on-site experiments was used to compare and analyze the distribution characteristics of the plastic zone of tunnel surrounding rock, deformation characteristics of tunnel surrounding rock, and stress characteristics of tunnel support anchor bolts under two support methods: double-layer spray anchor mesh and single-layer spray anchor mesh with+ steel bar. Research findings indicate that adopting the single-layer spray anchor mesh with+ steel bar support method results in a more uniform distribution of the plastic zone at the top of the tunnel surrounding rock, with a smaller range. The settlement of the roof and bulging of the bottom plate in the roadway's surrounding rock, supported by a single-layer spray anchor mesh and steel bars, measure at 75.033mm and 82.165mm, respectively. Additionally, the internal bulging on both sides of the roadway's surrounding rock is recorded as 37.835mm and 37.470mm, respectively. On the other hand, when utilizing a double-layer spray anchor mesh for support, the settlement of the roof and bulging of the bottom plate in the roadway's surrounding rock are measured at 84.199mm and 85.255mm, respectively. Correspondingly, the internal bulging on both sides of the roadway's surrounding rock records measurements of 41.670mm and 41.756mm, respectively.